Developing English Material Through Picture Slide for Teaching Writing of Vocational School - Mariana, Tety (English Education Department STKIP Al Hikmah Surabaya, 2018)
The purpose of developing English material through picture slide is to develop English material in the form of pictures slide show in order to improve the competence of students in writing descriptive text for ten graders of Vocational High School. The development of this learning material is based on Borg and Gall's Research Development (R & D) concept theory by following steps design of needs analysis, material development, expert validation, pilot and final product. The result of the development of this product is a picture slide material. It can be used and developed as a medium of teaching English for students in order to improve their writing skill and increase the student's motivation to learn. The development of teaching material is able to provide different way in English learning especially in teaching English of writing descriptive text. Students have motivation in learning descriptive text in this case is to write a text. Teaching material through picture slide can be developed again in accordance with the needs of students by practitioners and English teachers